2020
DOI: 10.1108/mmms-03-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

MHD boundary layer heat and mass transfer flow of nanofluid through porous media over inclined plate with chemical reaction

Abstract: PurposeSteady-state mixed convection boundary layer flow, heat and mass transfer characteristics of Buongiorno's model nanofluid over an inclined porous vertical plate with thermal radiation and chemical reaction are presented in this analysis.Design/methodology/approachThe governing nonlinear partial differential equations represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 53 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Upreti and Kumar (2020) investigated the MHD mixed convection on boundary layer flow of nano-fluid. Reddy and Sreedevi (2021) explained steady state mixed convective thermal energy and mass transport on boundary layer. Sivasankaran and Pan (2012) explored convective flow in geometries with non-uniform heating on the vertical walls of a solid lid (combined with convection).…”
Section: Introductionmentioning
confidence: 99%
“…Upreti and Kumar (2020) investigated the MHD mixed convection on boundary layer flow of nano-fluid. Reddy and Sreedevi (2021) explained steady state mixed convective thermal energy and mass transport on boundary layer. Sivasankaran and Pan (2012) explored convective flow in geometries with non-uniform heating on the vertical walls of a solid lid (combined with convection).…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found that the influence of aligned magnetic field have increase the velocity, skin friction and Nusselt number. In this way, several researchers did the investigation the effect of MHD under different situations [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of escalating nonlinear thermal radiation on boundary layer flow of several nanofluids is explored by Mahanthesh et al, [4]. The strengthening of the heat transmission rate with regular carrier liquids is highlighted in distinct scholarly articles pertaining to nano liquids [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%